1997
DOI: 10.3168/jds.s0022-0302(97)75995-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dystocia on Yield, Fertility, and Cow Losses and an Economic Evaluation of Dystocia Scores for Holsteins

Abstract: Lactation records of US Holstein cows were analyzed with mixed models to determine the effect of dystocia on 305-d milk, fat, and protein yields, days open, number of services, and cow losses and to estimate the economic loss associated with dystocia. The data were 122,715 records of 71,618 cows from 1980 to 1991. The single-trait animal model included herd-year-season, sex of calf, age of dam, and dystocia score as fixed effects and animal and permanent environment as random effects. The effect of dystocia wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
186
1
10

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(215 citation statements)
references
References 15 publications
18
186
1
10
Order By: Relevance
“…The proportion of cows that received assistance at calving, 18.0%, across dairy and beef cows, is within the ranges reported by Mee (2008) from studies reviewed across nine countries on dairy cows and heifers. The average twinning rate varied across maturity categories from 2% to 4%, which is similar to (inter)national estimates (Dematawewa and Berger, 1997;Silva del Rio et al, 2007;Mee et al, 2008). The overall sex ratio in this study across all maturity categories, with the exception of cows was 50.4% males, 49.6% females.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of cows that received assistance at calving, 18.0%, across dairy and beef cows, is within the ranges reported by Mee (2008) from studies reviewed across nine countries on dairy cows and heifers. The average twinning rate varied across maturity categories from 2% to 4%, which is similar to (inter)national estimates (Dematawewa and Berger, 1997;Silva del Rio et al, 2007;Mee et al, 2008). The overall sex ratio in this study across all maturity categories, with the exception of cows was 50.4% males, 49.6% females.…”
Section: Discussionsupporting
confidence: 80%
“…There was also a marked decrease in the kilograms of fat and protein produced in lactations after difficult calvings. Dematawewa and Berger (1997) have pointed to average losses of 703.6 kg in lactations after extremely difficult calvings. The cost of labour and veterinary assistance should be added to this loss.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate monitoring of pregnancies may lead to prolongation of the expulsive phase and an increase in perinatal death rates. Studies on Holstein cows have shown that calving complications cause reduced reproductive performance, resulting in a longer period between calving and conception (Dematawewa and Berger 1997). Various protocols have been proposed to determine the exact moment during which the calving process begins, including ultrasound monitoring (Wright et al 1988), observing changes in body temperature (Fujomoto et al 1988;Aoki et al 2005), analyzing blood levels of estrone sulfate and 17-ß-estradiol (Shah et al 2007), analyzing blood levels of progesterone (Matsas et al 1992), controlling the level of relaxation of pelvic ligaments (Dufty 1971), and determining the concentration of electrolytes present in mammary gland secretions (Bleul et al 2006).…”
Section: Introductionmentioning
confidence: 99%